Minigenes for heterologous expression of human and mouse cationic trypsinogen - Gergő Berke; Miklós Sahin-Tóth (PLoS ONE, 2026)
Inborn mutations in the PRSS1 gene encoding human cationic trypsinogen cause hereditary pancreatitis. In mouse models, PRSS1 mutations are often studied in the context of the Prss3b gene that codes for mouse cationic trypsinogen. To characterize the cellular and biochemical effects of trypsinogen mutations, heterologous expression in transfected cell lines is often employed. Recent studies with the human and mouse trypsin inhibitor SPINK1 indicated that minigene expression constructs carrying a short intron yield markedly higher recombinant protein levels than cDNA constructs. Here, we investigated whether the minigene approach would increase the expression of human and mouse cationic trypsinogen in transfected HEK 293T cells. We found that compared with the cDNA, minigene constructs increased PRSS1 and Prss3b mRNA levels by 2.5-fold and 4.5-fold on average, respectively. Surprisingly, however, the amount of secreted human cationic trypsinogen remained unchanged while secretion of mouse cationic trypsinogen was increased 2.9-fold. The observations indicate that minigene expression constructs are effective in boosting mRNA levels in transfected cells, however, this may not always translate to elevated protein secretion. In these cases, inefficient protein translation and/or folding may be rate limiting.